The integration of instructional technology by teacher educators at a state university in Zimbabwe: are they leading by example? - Chitanana, Lockias (Zimbabwe Journal of Educational Research, 2019)
The argument put up in this study is that if teachers have to use instructional technology in their classroom, they have to see lecturers modelling the best practices in technology utilisation. As such, the purpose of the study was to investigate the use of instructional technology by teacher educators in the Faculty of Education at Midlands State University (MSU) as a way of identifying good and poor practices of technology use in teacher education. The study used both quantitative and qualitative data. Eighteen (18) university lecturers in the Faculty of Education responded to a questionnaire. Follow-up interviews and observations were conducted with 8 lecturers selected from those participating to provide more in-depth information. The data was analysed to provide a description of how teacher educators used instructional technology at the university, their conception of instructional technology, their perceived levels of technical and pedagogical competences, and the major hindrances to their use of instructional technology. The findings show a limited view and moderate utilisation of instructional technology by teacher educators. The reasons for this stem from limited technical and pedagogical skills, as well as unavailability of the technology tools. This study recommends that, if trained teachers have to develop competence in the use of instructional technology, it is essential that efforts are made to upgrade the instructional technology capacity of the Faculty of Education through the provision of technology and professional development.